Investigation of influence of Lapes landfill leachate on ground and surface water pollution with heavy metals - Jaskelevičius, Bronius; Lynikienė, Vaida (Journal of Environmental Engineering and Landscape Management, 2009)
As a result of global and intense production the waste disposal problems become more and more urgent. Waste processing, utilization and recycling is to a certain extent limited by many economic, organisational and technological factors, and this inevitably encourages waste disposal in landfills. Physical, chemical and biological interactions in landfill cell result in formation of landfill gas and harmful leachate. Because of lack of control, together with usual communal waste, industrial waste was also dumped to landfills, therefore gas and leachate produced include large amounts of toxic compounds. Once hazardous waste materials occured in landfills, later they vastly expanded the whole spectrum of toxic materials and compounds. In the landfill environment chemical properties of surface and ground water and concentration of separate components are governed by seepage of leachate and industrial solutants into soil and ground layers and their transport by subsurface waters. Influence on the environment exerted by heavy metals contained in the leachate of Lapes Landfill is discussed in this paper. Properties of industrial waste material influenced order of the main pollutants: the most important elements in this case are Cu, Ni, Zn, Pb, Mn, Cr and other ions, the sulphides of these metals and other toxic compounds. The First Landfill field is more polluted with heavy metal polutants than the Third field. In all the samples iron concentration is the greatest exceeding even 200 times the admissible value allowed (Norm HN 24:2003). Sources (springs) S11 and S17 are least contaminated with heavy metals. The greatest groundwater pollution was found in monitoring bore G13s. The leachate processed in purification devices is released to the Third stream. Heavy metal concentrations in waters of this stream are low and they further decrease downstream because the pollutants are diluted.Reikšminiai žodžiai: sąvartynas, filtratas, sunkieji metalai, pH, koncentracija, gręžinys, gruntinis vanduo, paviršinis vanduo.Lapių sąvartyno filtrato įtakos aplinkos paviršinių ir požeminių vandenų užterštumui sunkiaisiais metalais tyrimaiSantrauka. Masiškai gaminant produkciją, ją vartojant, vis opesnė tampa atliekų problema. Atliekų perdirbimą, utilizavimą iš dalies ribojantys ekonominiai, organizaciniai bei technologiniai veiksniai neišvengiamai skatina atliekas šalinti į sąvartynus. Dėl sąvartyno tūryje vykstančių fizinių, cheminių bei biologinių reakcijų susidaro sąvartyno dujos ir kenksmingas filtratas. Kadangi dėl nepakankamos kontrolės į sąvartynus kartu su buitinėmis, komunalinėmis atliekomis buvo šalinamos pramonės atliekos, susidarančiose dujose bei filtrate yra daug toksiškų junginių. Šią toksinių medžiagų bei junginių įvairovę dar labiau papildo į sąvartynus patenkančios pavojingos atliekos. Gruntinio ir paviršinio upelių vandens cheminę sudėtį ir kai kurių komponentų koncentraciją sąvartyno aplinkoje lemia filtrato ir pramoninių tirpalų įsisunkimo į gruntą mastas bei požeminių tėkmių pernašos. Straipsnyje nagrinėjama Lapių sąvartyno filtrate aptiktų sunkiųjų metalų įtaka aplinkai. Pramonės atliekos lėmė, kad filtrato pagrindiniai teršiantieji elementai yra Cu, Ni, Zn, Pb, Mn, Cr ir kt. jonai, šių metalų sulfidai ir kiti toksiniai junginiai. Pirmasis kaupimosi laukas yra labiau užterštas sunkiaisiais metalais nei trečiasis laukas. Visuose mėginiuose didžiausia yra geležies koncentracija. Ji net iki 200 kartų viršija HN 24:2003 leidžiamąją normą. Mažiausiai sunkiaisiais metalais užteršti šaltiniai (S11 ir S17 postai). Požeminis vanduo labiausiai užterštas G13s gręžinyje. Iš valymo įrenginių išvalytas filtratas yra išleidžiamas į upelį. Šio upelio vandenyje rastų sunkiųjų metalų koncentracijos yra nedidelės, o upeliui tekant tolyn teršalai atskiedžiami, ir metalų koncentracijos mažėja.Исследование загрязнения поверхностных и подземных вод тяжелыми металлами из фильтрата свалки в ЛапесРезюме. Массовое производство продукции, пользование ею все более обостряют проблему отходов. Процессы переработки и утилизации отходов, в определенной степени ограничивающие экономические, организационные и технологические факторы, неизбежно способствуют интенсификации удаления отходов на свалки. На свалках отходов в результате протекающих физических, химических и биологических реакций образуются газы и токсичный фильтрат. Поскольку из-за недостаточного контроля на свалку вместе с бытовыми, коммунальными отходами удалялись и промышленные отходы, в составе образующихся газов и фильтрата имеется много токсичных соединений. Опасные отходы еще более увеличили спектр токсичных материалов и соединений в газах и фильтрате свалки. Химический состав и концентрация отдельных компонентов грунтовых и поверхностных вод в районе свалки определяют проникновение фильтрата и промышленных растворов в грунт и их перенос подземными течениями. В статье изучается влияние тяжелых металлов из фильтрата свалки в Лапес на состояние вод в районе свалки. Промышленные отходы способствовали появлению в фильтрате ионов основных загрязняющих элементов Cu, Ni, Zn, Pb, Mn, Cr, сульфидов этих металлов и других токсичных соединений. Первое поле накопления отходов в большей степени загрязнено тяжелыми металлами, чем третье поле. Во всех опытных образцах воды отмечена самая большая концентрация ионов железа, почти в 200 раз превышающая допустимую норму HN 24:2003. Наименьшее загрязнение тяжелыми металлами отмечено в подземной воде источников (посты S11 и S17). Грунтовые воды больше всего загрязнены в скважине G13s. Поверхностные воды ручьев, в которые проникает фильтрат, а также сливается очищенный фильтрат, содержат небольшие концентрации тяжелых металлов, которые разбавляются течением и уменьшаются.Ключевые слова: свалка, фильтрат, тяжелые металлы, pH, концентрация, скважина, грунтовые воды, поверхностные воды.First Published Online: 14 Oct 2010